Prototheca wickerhamii Cutaneous and Systemic Infections - Chou, Deng-Wei (The American Society of Tropical Medicine and Hygiene, 2014)
Prototheca wickerhamii, an environmental alga, rarely causes human infections. We present a case of Prototheca wickerhamii cutaneous and systemic infections in an 85-year-old male with adrenal insufficiency. This organism was identified by morphological features and microbiological tests. The patient was successfully treated with ketoconazole.